How Unilever Indonesia Uses Digital Marketing To Drive Brand Growth And Boost Profits - Rayhan Dwirafama,; Rafly Hermansyah,; Cikal Barts Rinan,; Haryadi Sarjono, (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Amid rapid digital advancements, companies must adapt to remain competitive. PT Unilever Indonesia Tbk, a leading multinational in the Fast-Moving Consumer Goods (FMCG) sector, has successfully adopted digital marketing strategies to boost brand awareness and strengthen its market position in Indonesia. This study aims to: identify Unilever’s digital marketing strategies to enhance brand awareness; analyze the effectiveness of social media platforms such as Instagram, TikTok, and YouTube in improving brand recognition and recall; examine how creative, interactive, and storytelling-based content increases consumer engagement; and assess the overall impact of these strategies on Unilever’s market reach, consumer loyalty, and financial performance. Using a descriptive qualitative approach and secondary data analysis, this study evaluates Unilever's digital campaigns across various platforms. The findings show that Unilever’s digital marketing efforts are effective in increasing brand awareness and strengthening brand positioning. Campaigns on social media have successfully engaged consumers through relevant, creative, and relatable content. While there was a decline in the Inventory Turnover ratio and ROI between 2020 and 2022, this indicates that digital marketing strategies require time to deliver measurable financial outcomes. Nonetheless, their long-term contribution to efficiency, profitability, and brand equity is promising.